The Effects of Dietary Glycine on the Acetic Acid-Induced Mouse Model of Colitis - Xin Wu; Yongmin Zheng; Jie Ma; Jie Yin; Shuai Chen (Hindawi Limited, 2020)
Inflammatory bowel disease, a gut disease that is prevalent worldwide, is characterized by chronic intestinal inflammation, such as colitis, and disorder of the gut microbiome. Glycine (Gly) is the simplest amino acid and functions as an anti-inflammatory immune-nutrient and intestinal microbiota regulator. This study aimed at investigating the effect of Gly on colitis induced in mice by intrarectal administration of 5% acetic acid (AA). Bodyweight and survival rates were monitored, and colonic length and weight, serum amino acid concentrations, intestinal inflammation-related gene expression, and colonic microbiota abundances were analyzed. The results showed that Gly dietary supplementation had no effect on the survival rate or the ratio of colonic length to weight. However, Gly supplementation reversed the AA-induced increase in serum concentrations of amino acids such as glutamate, leucine, isoleucine, and valine. Furthermore, Gly inhibited colonic gene expression of interleukin- (IL-) 1β and promoted IL-10 expression in colitis mice. Gly supplementation also reversed the AA-induced reduction in the abundance of bacteria such as Clostridia, Ruminococcaceae, and Clostridiales. This change in the intestinal microbiota was possibly attributable to the changes in colonic IL-10 expression and serum concentrations of valine and leucine. In sum, Gly supplementation regulated the serum concentrations of amino acids, the levels of colonic immune-associated gene expression, and the intestinal microbiota in a mouse model of colitis. These findings enhance our understanding of the role of Gly in regulating metabolism, intestinal immunity, and the gut microbiota in animals afflicted with colitis.